Genome-wide identification of YABBY gene family and its expression pattern analysis in Astragalus mongholicus - Jiamei Wang; Zhen Wang; Panpan Wang; Jianhao Wu; Lingyang Kong; Lengleng Ma; Shan Jiang; Weichao Ren; Weili Liu; Yanli Guo; Wei Ma; Xiubo Liu (Plant Signaling & Behavior)
During plant growth and development, the YABBY gene plays a crucial role in the morphological structure, hormone signaling, stress resistance, crop breeding, and agricultural production of plant lateral organs, leaves, flowers, and fruits. Astragalus mongholicus is a perennial herbaceous plant in the legume family, widely used worldwide due to its high medicinal and edible value. However, there have been no reports of the YABBY gene family in A. mongholicus. This study used bioinformatics methods, combined with databases and analysis websites, to systematically analyze the AmYABBY gene family in the entire genome of A. mongholicus and verified its expression patterns in different tissues of A. mongholicus through transcriptome data and qRT-PCR experiments. A total of seven AmYABBY genes were identified, which can be divided into five subfamilies and distributed on three chromosomes. Two pairs of AmYABBY genes may be involved in fragment duplication on three chromosomes. All AmYABBY proteins have a zinc finger YABBY domain, and members of the same group have similar motif composition and intron – exon structure. In the promoter region of the genes, light-responsive and MeJa-response cis-elements are dominant. AmYABBY is highly expressed in stems and leaves, especially AmYABBY1, AmYABBY2, and AmYABBY3, which play important roles in the growth and development of stems and leaves. The AmYABBY gene family regulates the growth and development of A. mongholicus. In summary, this study provides a theoretical basis for in-depth research on the function of the AmYABBY gene and new insights into the molecular response mechanism of the growth and development of the traditional Chinese medicine A. mongholicus.